Effects of Heat Treatments on Magnetoimpedance of Fe40Ni38Mo4B18 Ribbons - Pongsakorn Jantaratana,; Saisunee Pasuksan, (Agriculture and Natural Resources, 2009)
The magnetoimpedance effect in Fe40Ni38Mo4B18 ribbons was studied as a function of the frequency of the driving current and the static magnetic field. The as-cast sample exhibited single peak magnetoimpedance with small hysteresis in the low magnetic field regime. The conventional furnace annealing led to magnetic hardening and a decrease in the magnetoimpedance ratio. However, furnace annealing also induced transverse magnetic anisotropy and increased the magnetic field sensitivity. The maximum field sensitivity of 6%/Oe for the as-cast sample increased to more than 14 %/Oe after being annealed at 200°C. The magnetoimpedance of the samples can be explained by the frequency of the current and magnetic field dependence on the transverse magnetic permeability of the soft ferromagnetic conductor.